The Influence of System Digitalization and Logistics Transformation on Performance with Moderation of Technological Competency at PT. Defour Naga Jaya - Hutagalung, Immanuel; Lukiyana; Soetiyani, Ari (Journal of Business and Behavioural Entrepreneurship, 2024)
This study aims to understand the impact of system digitalization and logistics transformation on employee performance , with technological competence as a moderating variable at PT. Defour Naga Jaya. The Partial Least Squares Structural Equation Modeling (PLS-SEM) method was used to analyze data from 185 employee performance respondents in Jakarta. The results showed that system digitalization and logistics transformation have a positive and significant effect on employee performance . Technological competence significantly moderates this relationship, strengthening the benefits gained from digitalization and logistics transformation. However, the moderating effect on logistics transformation is more complex, with some significant negative effects. This study highlights the importance of employee training, investment in technology infrastructure, and management commitment to technological innovation. These findings provide strategic insights for companies in the logistics sector to improve operational efficiency, competitiveness, and long-term sustainability. Limitations of the study include limited generalization, and recommendations for further research include expanding variables and industry contexts.